The Texas State Plan for the Education of Homeless Children and Youth - Texas Education Agency, Austin. Div. of Special Programs; Texas Education Agency, Austin. Div. of Special Programs ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Texas's state plan for homeless education is presented in response to requirements of Title VII-B of the Stewart B. McKinney Homeless Assistance Act of 1987. The plan is comprised of prefatory material, four main sections, and four appendices. The prefatory material consists of the following parts: (1) a prefatory statement; (2) a copy of the federal assistance form for Texas; (3) assurances of compliance; and (4) budget information. The first section, "Definitions," defines the following terms: (1) "homeless children and youth"; (2) "free and appropriate public education"; and (3) "school-age." The second section, "Statement of the Problem," enumerates 22 difficulties for homeless education within the following categories: (1) barriers to data collection; (2) barriers to enrollment; and (3) barriers to attendance and success in school. The third section, "Objectives and Activities," describes goals in the following areas: (1) data collection; (2) residency and guardianship requirements; (3) school choice and dispute resolution; (4) unexcused absences policy; (5) parent awareness and participation; (6) school personnel sensitivity; (7) development of a best practices manual; (8) inter-agency coordination; and (9) a homebound services feasibility study. The following appendices are included: (1) a list of Advisory Task Force members; (2) sample strategies and systems; (3) a copy of Subtitle VII-B of the McKinney Act; and (4) a student record data collection form. (AF)
ERIC Note: Some pages contain marginally legible print.
Administrators.
Policymakers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Disadvantaged Youth; Educational Legislation; Elementary Secondary Education; Federal Legislation; Federal Programs; Homeless People; Program Administration; Program Implementation; Social Services; State Federal Aid; State Programs; Student Needs; Student Problems; Student Welfare; Stewart B McKinney Homeless Assistance Act 1987 -- Texas; Legal/Legislative/Regulatory Materials; Reports, Descriptive